Teoretske refleksije Pax Americane: vloga ZDA v povojnih ekonomskih režimih - Andolšek, Matej (Teorija in praksa, 1998)
According to the theory of hegemonic stability, stability of world economy depends on the presence of a hegemon. The purpose of the article is to explain how hegemon creates multilateral arrangements (international regimes) to provide public goods and distribute costs of stabilizing world economy. After the Second World War (Pax Americana), such arrangements were established in order to regulate international trade and finance. Creation of international regimes is related to the problem of international cooperation, hampered by the effects of anarchic international (interstate) system. Through international regimes hegemon sets standards of behaviour in order to reduce uncertainty, and thus promoting cooperation.
Keywords: United States of America; ZDA; mednarodni ekonomski odnosi; mednarodni odnosi; hegemonija; politična ekonomija